Influence of unevenness of airport pavements on technical condition and safety of air operations - Adam Poświata; Paweł Pietruszewski; Piotr Włodarski (Przegląd Komunikacyjny)
Abstract: The publication presents the requirements for airport pavements for the assessment of the evenness of airport pavements, including the methodology of testing unevenness. On the basis of the selected aircraft type, the impact of unevenness on the dynamic interaction of the plane - pavement was determined, and the vertical displacements occurring at the edges of concrete slabs were taken for analysis. The paper presents the influence of operational procedures in the form of pavement grooving and local surface repairs on the results of unevenness measurements and improvement of the technical condition of the pavement, as well as on the safety of air operations. Keywords: Pavement unevenness; Evaluation criteria; Dynamic action plane - surface; Grooving pavement; Maintenance treatments; The functional element of the airport